2002
DOI: 10.1080/01140671.2002.9514221
|View full text |Cite
|
Sign up to set email alerts
|

Inoculum sources and infection pathways of pathogens causing stem‐end rots of ‘Hass’ avocado(PerseaAmericana)

Abstract: Species of Colletotrichum, Botryosphaeria, and Phomopsis causing postharvest rots in avocado (Persea americana Miller) fruits are present in the living and dead branches and twigs of avocado trees, and in the living pedicels. They dominate the fungal population within the extra-cambial tissues but are less common within the xylem elements. There is no evidence that invasion of these tissues is pathogenic. With the possible exception of C. gloeosporioides they appear to be discontinuously present and are more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 12 publications
2
33
1
1
Order By: Relevance
“…Recently, Twizeyimana et al (2013) showed that the pathogens causing cankers may be a source of inoculum for stem-end rot. Conversely, fungal species associated with stem-end rot could cause branch cankers (Hartill and Everett 2002;Menge and Ploetz 2003). In Mediterranean environments, pathogens belonging to the fungal groups mentioned previously are reported to cause diseases on a range of woody plants species and their fruit.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Recently, Twizeyimana et al (2013) showed that the pathogens causing cankers may be a source of inoculum for stem-end rot. Conversely, fungal species associated with stem-end rot could cause branch cankers (Hartill and Everett 2002;Menge and Ploetz 2003). In Mediterranean environments, pathogens belonging to the fungal groups mentioned previously are reported to cause diseases on a range of woody plants species and their fruit.…”
Section: Introductionmentioning
confidence: 96%
“…Frost-or mechanical injuries such as pruning wounds may allow these canker-causing pathogens access to initiate infection. Various species of the Botryosphaeriaceae cause stem-end rot of avocado (Hartill and Everett 2002;Menge and Ploetz 2003). Stem-end rot starts as a dark-brown to black rot at the stem-end of the fruit with darkening of the internal vascular bundles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruits play an important role in socioeconomic. Surveys conducted by Hartill and Everett (2002), Everett et al (2007) showed that anthracnose, stem rot, galls, fruit spot and fruit rot were the most important fungal diseases. The incidence of these diseases can be up to 90% in areas with high relative humidity (COLEACP, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These pathogens have a wide host range and may have originated from infected host material already present in New Zealand or from infected avocado plant material imported in 1907, 1917 and 1940. Most fungi that infect fruit to cause rots will also asymptomatically infect vegetative tissue (Everett et al 1999;Hartill & Everett 2002;Everett et al 2003). The first record of an avocado fruit rot was of C. gloeosporioides Pathogens 1 (Brien 1939), and the first record of a root disease was of Phytophthora cinnamomi (Zentmeyer 1965), then the vascular wilt pathogen V. dahliae (Fletcher 1976).…”
Section: Introductionmentioning
confidence: 99%